PERILAKU PENJAMAH MAKANAN WARUNG MAKAN PADA MASA PANDEMI COVID-19 - Dyah Suryani; Karina Widyastuti (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Al Asyariah Mandar, 2022)
Not all foods are safe to consume, especially during the Covid-19 pandemic. Food stalls are one of the places to meet food needs. The behavior of food handlers becomes a key to food safety that is likely to be influenced by education, attitudes, level of education and training. This study aims to determine the relationship between knowledge, attitudes, levels of education and training with the behavior of food stall handlers during the Covid-19 pandemic. The type and design of the research are cross-sectional observations. The number of samples, as many as 52 food handlers taken with the total sampling technique. The data was taken using a questionnaire. The data analysis using Fisher's exact CI of 95% (α = 0.05). The results of the study found that there is no relationship between knowledge (p-value = 0.444), attitude (p-value = 0.180), education level (p-value = 0.228) and the behavior of food handlers. In addition, there is a relationship between training (p-value=0.001) and the behavior of food handlers. There is no relationship between knowledge, attitude, level of education and food handlers' behavior at food stalls during the Covid-19 pandemic. There is a relationship between training and food handler behavior at food stalls during the Covid-19 pandemic.